Wahabism: a misconception segregating the Malay Muslim community and Wasatiyyah as the mean for an ideal life - Junid, Humairah; Abdul Rahim, Adibah (2017)
This paper seeks to study the misconception of Wahhabism that prevails within the Malay Muslim community in the 21st century and aims to explain that the Wahhabi movement is a misnomer with reference to the renowned scholar Muhammad Ibn Abdul Wahhab. This study examines the mission of Muhammad Ibn Abdul Wahhab and comes to learn the history of the term Wahhabi. Malays dispel Wahhabism for they are not bilateral with Sunnis thought but people whom proudly associate themselves with the Wahhabi movement contributed to fuel the confusion even further. The perplexity on the issue of Wahhabism needs to be addressed and this paper will also promote the practice of Wasatiyyah to enhance the social living of Malay Muslim community. To achieve the main purpose of this study, descriptive and analytical method has been applied. The findings of this research will help both the masses and ‘Wahhabis’ to properly put their puzzled pieces of thought in place regarding Wahhabism and it will also assist in improving the tension of the present Malay Muslim community.